Methodological problems in gender and media research - Capecchi, Saveria (Quality & quantity, 2014)
This paper will focus on the main questions that have arisen from a methodological point of view relating to the theoretical and research area of gender and media , which continues to be the subject of discussion and debate. The methodology chosen by scholars has changed over the course of time, depending on: the interpretative paradigm underlying the researchers (especially from the feminist perspective which leads the analysis, due to the theme); the sociocultural context; the type of contents offered by the media ( old, new media ); and technological innovations in the communications field. In particular, the author underlines that scholars who adopt the equality between the sexes perspective tend to favour quantitative methods, while scholars oriented towards highlighting sexual and gender differences tend to favour qualitative methods.